2015
DOI: 10.1097/gco.0000000000000221
|View full text |Cite
|
Sign up to set email alerts
|

Rotational vaginal delivery with Kielland's forceps

Abstract: Kielland's forceps have a high success rate with relatively low adverse outcomes despite their use being controversial. In comparison to rotational ventouse, Kielland's forceps have higher efficacy with less risk of neonatal trauma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(7 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…The findings of our study are comparable with the findings of a previous systematic review conducted by Al‐Wattar et al., in which the authors compared the rates of complications in pregnancies with KRFD to pregnancies that delivered by RVD 21 . They reported that KRFD was associated with a lower rate of neonatal birth trauma in comparison with RVD (RR 0.62, 95% CI 0.46–0.85, p = 0.003), which is similar to the results of our study, which demonstrated a 50% lower chance of neonatal birth trauma in pregnancies with KRFD, compared with RVD (RR 0.49, 95% CI 0.26–0.91, p = 0.024).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The findings of our study are comparable with the findings of a previous systematic review conducted by Al‐Wattar et al., in which the authors compared the rates of complications in pregnancies with KRFD to pregnancies that delivered by RVD 21 . They reported that KRFD was associated with a lower rate of neonatal birth trauma in comparison with RVD (RR 0.62, 95% CI 0.46–0.85, p = 0.003), which is similar to the results of our study, which demonstrated a 50% lower chance of neonatal birth trauma in pregnancies with KRFD, compared with RVD (RR 0.49, 95% CI 0.26–0.91, p = 0.024).…”
Section: Discussionsupporting
confidence: 91%
“…0.1 0.2 0.5 1 2 5 10 in pregnancies with KRFD to pregnancies that delivered by RVD. 21 They reported that KRFD was associated with a lower rate of neonatal birth trauma in comparison with RVD (RR 0.62, 95% CI 0.46-0.85, p = 0.003), which is similar to the results of our study, which demonstrated a 50% lower chance of neonatal birth trauma in pregnancies with KRFD, compared with RVD (RR 0.49, 95% CI 0.26-0.91, p = 0.024). Al-Watter et al also reported no statistically significant difference in the F I G U R E 5 Forest plot demonstrating summary statistics for risk of shoulder dystocia in pregnancies delivering by Kielland's rotational forceps delivery (KRFD), compared with pregnancies delivering by rotational ventouse delivery (RVD) and non-rotational forceps delivery (NRFD).…”
Section: Comparison With Other Studiesmentioning
confidence: 99%
“…As in the current study, other two reported cases of neonatal deaths were performed by very experienced obstetricians that performed successful Kielland's forceps before and after the incident. In recent systematic review, Wattar et al reported 0.3% perinatal mortality rate associated with use of Kielland's forceps, though he attributed reported deaths to other factors such as congenital abnormalities, intrapartum asphyxia, and prematurity [15]. This may explain why Bertholdt et al, in 2022, advocated use of instrumental rotation with either vacuum or forceps only after manual rotation failure [16].…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review of observational studies comparing rotational forceps versus rotational vacuum extraction demonstrated lower neonatal trauma rates (RR 0.62 (0.46-0.85, p = 0.003)) and a substantially lower failure rate (5.4% vs. 16%, RR 0.32 (0.14-0.76, p = 0.009)) with the KRF. The same review found no differences in the incidence of postpartum hemorrhage, anal sphincter injury (OASI), or extensive vaginal or cervical injury [36]. Meta-analysis was only possible for a small subset of outcomes, highlighting that further research is needed to study these outcomes.…”
Section: Rotational Forcepsmentioning
confidence: 99%